WHATSAPP MESSENGER DATA BACKUP AND RECOVERY ANALYSIS USING MOBILEDIT FORENSIC EXPRESS AND DR.FONE - Prasetio Prasetio; Aswandi Aswandi; Ilham Safar (Politeknik Negeri Lhokseumawe, 2025)
This research is motivated by how to backup data and recover data that has been lost due to carelessness or user error in using this WhatsApp messenger application, this research aims to Backup and Recover data on the WhatsApp messenger application that has been deleted, lost data, failure, and damage (failure). The results of the study show that the Mobiledit Forensic Express application has different levels of success in backing up and recovering data. This application cannot recover conversation data that has a percentage (50%), but is able to backup and recover various WhatsApp data such as; Links, Status, WhatsApp Animated Gifs, WhatsApp Audio, WhatsApp Documents, WhatsApp Images, WhatsApp Sticker, WhatsApp Video, WhatsApp Video Notes, and WhatsApp Voice Notes (100%) data that can be backed up and recovered by the Mobiledit Forensic Express application. While the Dr.Fone application can backup data and recover WhatsApp chat data with a percentage (80%), but data such as WhatsApp attachments (Audio, Documents, Images, Stickers, Videos, and Voice Notes) only get (50%) because it can only recover new and undamaged photos or videos from the WhatsApp application. By comparing or searching for which applications are relevant for conducting research can help the forensic team and can make it easier for those who want to backup data and recover data in the WhatsApp application using applications that support this research, Mobiledit Forensic Express and Dr.Fone.